Healthcare-associated infections and antimicrobial use in surgical wards of a large urban central hospital in Blantyre, Malawi: a point prevalence survey. Issue 3 (September 2021) - Bunduki, Gabriel Kambale; Feasey, Nicholas; Henrion, Marc Y.R.; Noah, Patrick; Musaya, Janelisa
Summary: Background: There are limited data on healthcare-associated infections (HAI) from African countries like Malawi. Aim: We undertook a point prevalence survey of HAI and antimicrobial use in the surgery department of Queen Elizabeth Central Hospital (QECH) in Malawi and ascertained the associated risk factors for HAI. Methods: A cross-sectional point prevalence survey (PPS) was carried out in the surgery department of QECH. The European Centre for Disease Prevention and Control PPS protocol version 5.3 was adapted to our setting and used as a data collection tool. Findings: 105 patients were included in the analysis; median age was 34 (IQR: 24–47) years and 55.2% patients were male. Point prevalence of HAI was 11.4% (n=12/105) (95% CI: 6.0%–19.1%), including four surgical site infections, four urinary tract infections, three bloodstream infections and one bone/joint infection. We identified the following risk factors for HAI; length-of-stay between 8 and 14 days (OR=14.4, 95% CI: 1.65–124.7, p=0.0143), presence of indwelling urinary catheter (OR=8.3, 95% CI: 2.24–30.70, p=0.003) and history of surgery in the past 30 days (OR=5.11, 95% CI: 1.46–17.83, p=0.011). 29/105 patients (27.6%) were prescribed antimicrobials, most commonly the 3rd-generation cephalosporin, ceftriaxone (n=15). Conclusion: The prevalence rates of HAI and antimicrobial use in surgery wards at QECH are relatively high. Hospital infection prevention and control measures need to be strengthened to reduce the burden of HAI at QECH.